2000
DOI: 10.1111/j.1095-8649.2000.tb02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of maturation and spermiation in the male European eel: assessment of sperm quality throughout treatment

Abstract: Weekly injections of human chorionic gonadotropin (hCG; 1·5 IU g 1 W) induced spermiation in 87-100% farmed male European eels Anguilla anguilla over a 10-week period, producing 3 ml (100 g) 1 milt volume, at 1·4 10 9 spermatozoa ml 1 sperm mobility peaked in ninth week of treatment with 97% of males with motile sperm. Gonadotropin-treated males showed earlier but similar morphological changes to control males. Whereas higher sperm density was obtained 6 h after hCG administration, higher percentage of motile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
131
3
17

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(158 citation statements)
references
References 40 publications
7
131
3
17
Order By: Relevance
“…Sperm samples were collected weekly 24 h after administering the hormonal treatment, in order to 137 achieve the highest sperm quality (Pérez et al, 2000). Fish were anesthetized and the genital area was 138 cleaned with freshwater and thoroughly dried to avoid the contamination with feces, urine or sea water.…”
Section: Sperm Collection 136mentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm samples were collected weekly 24 h after administering the hormonal treatment, in order to 137 achieve the highest sperm quality (Pérez et al, 2000). Fish were anesthetized and the genital area was 138 cleaned with freshwater and thoroughly dried to avoid the contamination with feces, urine or sea water.…”
Section: Sperm Collection 136mentioning
confidence: 99%
“…The 475 effectivity of gonadotropins to induce spermiation seems to be due to their LH-like effect and the 476 modulation of hypothalamic-pituitary-gonadal axis. Several studies have shown that the onset of 477 spermiation depends on a peak in LH plasma levels, which causes consecutive increases in androgen 478 synthesis and a shift to MIS production (Asturiano et al, 2000(Asturiano et al, , 2002. MIS have important effects in the 479 final phase of sperm maturation, causing sperm hydration and therefore an increase of its volume and 480 testicular size (Asturiano et al, 2002(Asturiano et al, , 2004 Peñaranda et al, 2010b).…”
mentioning
confidence: 99%
“…Due to the fact that the eels do not mature sexually in captivity there have been developed methods for the hormonal induction that achieve the production of important volumes of sperm of good quality (Pérez et al 2000;Müller et al 2004). This fact has motivated the interest to develop techniques for the compilation and appropriate managing of the sperm of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Con esto se pretendía optimizar tratamientos hormonales usados anteriormente y buscar tratamientos de inducción más cortos, con períodos más largos de producción de semen, menor manipulación de los peces y una mejor calidad del esperma. Los tratamientos fueron:• Tratamiento A: consistió en la administración semanal de 1.5 UI hCG/g pez durante 12 semanas (descrito previamente por Pérez et al 2000).• Tratamiento B: la dosis semanal de hormona suministrada a los peces fue de 0.75 UI hCG/g pez, equivalente a la mitad de la dosis del tratamiento A durante 12 semanas. …”
unclassified
See 1 more Smart Citation